Entrepreneurship Selection and Performance - Justin van der Sluis; Mirjam van Praag; Wim Vijverberg (Tinbergen Institute, 2003)
This meta-analytical review of empirical studies of the impact of schooling on entrepreneurship selection and performance in developing economies looks at variations in impact across specific characteristics of the studies. A marginal year of schooling in developing economies raises enterprise income by an average of 5.5 percent, which is close to the average return in industrial countries. The return varies, however, by gender, rural or urban residence, and the share of agriculture in the economy. Furthermore, more educated workers typically end up in wage employment and prefer nonfarm entrepreneurship to farming. The education effect that separates workers into self-employment and wage employment is stronger for women, possibly stronger in urban areas, and also stronger in the least developed economies, where agriculture is more dominant and literacy rates are lower.
Keywords: J23; J24; J31; M13; 330; Meta-analysis; schooling; education; entrepreneurship; self-employment; performance; occupational choice.; Bildungsertrag; Entrepreneurship-Ansatz; Selbstständige; Schätzung